Bridge and pathway leading to the Kaner-ki-Putli Temple - Temples of India Project Team (Jio Institute, 2024)
The present bridge and pathway leading to the Kaner-ki-Putli Temple have been reconstructed by the Jaipur Circle, Archaeological Survey of India (ASI). The bed of the fountain stream is visible below the bridge.